Sporotrichosis as an unusual case of osteomyelitis: A case report and review of the literature - Lederer, Henry T. (Med Mycol Case Rep, 2016)
Sporotrichosis is an infection of worldwide distribution caused by the dimorphic fungus, Sporothrix schenckii. Acquisition typically occurs via cutaneous inoculation with development of a localized cutaneous and/or lymphocutaneous infection. We present a rare case of osteoarticular sporotrichosis in a 39-year-old man and review the literature noting only 20 published cases since 1980. Recommendations on the diagnosis and management of this unusual infection are provided.